Evaluation of Faculty Readiness in Realizing Entrepreneurial University Agenda - Virna Vidya Yustita; Astri Ghina (Publikasi Indonesia, 2022)
Knowledge and changes in the higher education sector are currently contributing to socio-economic developments that encourage new forms of cooperation and the economy related to the process of globalization, social dynamics, and the development of a knowledge-based economy. Entrepreneurship in higher education is a fairly new concept. EU in the sense of three things: the university itself, the members of the university (faculty) and the interaction of the university with the environment. The selection of the object is based on the fact that FEB has quite a lot of Intellectual Property Rights (IPR) during 2016-2019. In this study, it aims to realize the economic and business framework of Telkom University in realizing the entrepreneurial university agenda, it must implement the EU dimension itself, there are 8 dimensions to realize the EU architecturally. This study uses a qualitative method with interview sources, namely FEB lecturers who have high positions such as deans, vice deans, and lecturers related to entrepreneurship. The results of this study prove that the Faculty of Economics and Business has many programs created by both of them but will support this EU activity, many dimensions need to be improved both from the website and information between students, lecturers and staff. Researchers provide various kinds of practical suggestions that architecture can do in improving and developing programs to support Entrepreneurial University activities.